Mycobacterium tuberculosis Peptidyl-Prolyl Isomerases Are Immunogenic, Alter Cytokine Profile and Aid in Intracellular Survival - Pandey, Saurabh; Tripathi, Deeksha; Khubaib, Mohd; Kumar, Ashutosh; Sheikh, Javaid A.; Sumanlatha, Gaddam; Ehtesham, Nasreen Z.; Hasnain, Seyed E. (Frontiers in Cellular and Infection Microbiology, 2017)
Mycobacterium tuberculosis (M. tb) has two peptidyl-prolyl isomerases (Ppiases) PpiA and PpiB, popularly known as cyclophilin A and cyclophilin B. The role of cyclophilins in processes such as signaling, cell surface recognition, chaperoning, and heat shock response has been well-documented. We present evidence that M. tb Ppiases modulate the host immune response. ELISA results revealed significant presence of antibodies to M. tb Ppiases in patient sera as compared to sera from healthy individuals. Treatment of THP-1 cells with increasing concentrations of rPpiA, induced secretion of pro-inflammatory cytokines TNF-α and IL-6. Alternatively, treatment with rPpiB inhibited secretion of TNF-α and induced secretion of IL-10. Furthermore, heterologous expression of M. tb PpiA and PpiB in Mycobacterium smegmatis increased bacterial survival in THP-1 cells as compared to those transformed with the vector control. Our results demonstrate that M. tb Ppiases are immunogenic proteins that can possibly modulate host immune response and enhance persistence of the pathogen within the host by subverting host cell generated stresses.